Nanocrystal Agglomerates of Curcumin Prepared by Electrospray Drying as an Excipient-Free Dry Powder for Inhalation - Shahram Emami; Zahra Hemmati; Shadi Yaqoubi; Hamed Hamishehkar; Amin Alvani (Advances in Pharmacological and Pharmaceutical Sciences)
Curcumin has shown beneficial effects on pulmonary diseases with chronic inflammation or abnormal inflammatory responses, including chronic obstructive pulmonary disease, asthma, and pulmonary fibrosis. Clinical applications of curcumin are limited due to its chemical instability in solution, low water solubility, poor oral bioavailability, and intestinal and liver first-pass metabolism. Pulmonary delivery of curcumin can address these challenges and provide a high concentration in lung tissues. The purpose of the current work was to prepare a novel inhalable dry powder of curcumin nanocrystals without added excipients using electrospray drying (ED) with improved dissolution and aerosolization properties. ED of curcumin was performed at 2 and 4% w/v concentrations in acetone. Physicochemical properties of the formulated powders were evaluated by powder X-ray diffraction (PXRD), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), density and powder flow measurements, and in vitro dissolution. The in vitro deposition studies were conducted using next-generation impactor (NGI) and aerosol performance and aerodynamic particle size parameters were calculated for prepared formulations. ED could produce agglomerates of nanocrystals with a size of about 500 nm at an acceptable yield of about 50%. PXRD and FTIR data revealed that prepared nanocrystals were in a stable crystalline state. The bulk and tapped density of prepared agglomerates were in the range appropriate for pulmonary delivery. Formed nanocrystals could significantly improve the dissolution rate of water-insoluble curcumin. The optimized formulation exhibited acceptable recovered dose percentage, high emitted dose percentage, optimum mean mass median aerodynamic diameter, small geometric standard deviation, and high fine-particle fraction that favors delivery of curcumin to the deep lung regions. The ED proved to be an efficient technique to prepare curcumin nanocrystals for pulmonary delivery in a single step, at a mild condition, and with no surfactant.